Immunoreactive Trypsinogen in Infants Born to Women with Cystic Fibrosis Taking Elexacaftor–Tezacaftor–Ivacaftor - Payal Patel; Jana Yeley; Cynthia Brown; Melissa Wesson; Barbara G. Lesko; James E. Slaven; James F. Chmiel; Raksha Jain; Don B. Sanders (International Journal of Neonatal Screening, 2023)
Most people with cystic fibrosis (CF) are diagnosed following abnormal newborn screening (NBS), which begins with measurement of immunoreactive trypsinogen (IRT) values. A case report found low concentrations of IRT in an infant with CF exposed to the CF transmembrane conductance regulator (CFTR) modulator, elexacaftor–tezacaftor–ivacaftor (ETI), in utero. However, IRT values in infants born to mothers taking ETI have not been systematically assessed. We hypothesized that ETI-exposed infants have lower IRT values than newborns with CF, CFTR-related metabolic syndrome/CF screen positive, inconclusive diagnosis (CRMS/CFSPID), or CF carriers. IRT values were collected from infants born in Indiana between 1 January 2020, and 2 June 2022, with ≥1 CFTR mutation. IRT values were compared to infants born to mothers with CF taking ETI followed at our institution. Compared to infants identified with CF (n = 51), CRMS/CFSPID (n = 21), and CF carriers (n = 489), ETI-exposed infants (n = 19) had lower IRT values (p < 0.001). Infants with normal NBS results for CF had similar median (interquartile range) IRT values, 22.5 (16.8, 30.6) ng/mL, as ETI-exposed infants, 18.9 (15.2, 26.5). IRT values from ETI-exposed infants were lower than for infants with abnormal NBS for CF. We recommend that NBS programs consider performing CFTR variant analysis for all ETI-exposed infants.